NATURAL FREQUENCY OF RC WALLS WITH VARIOUS SIZES AND LOCATIONS OF OPENING - HASSAN , HOGR; SAEED, NAJMADEEN; MANGURI, AHMED (Journal of Duhok University, 2023)
Reinforced concrete (RC) structural walls, also known as shear walls, are commonly employed as lateral force-resisting elements in structures located in areas with moderate-to-high seismic hazards. These walls significantly enhance a building's lateral strength and stiffness, enabling them to withstand heavy ground shaking. In certain cases, it may be necessary to incorporate openings in reinforced concrete shear walls to meet specific performance requirements. However, these openings can alter the force transmission mechanism, resistance, and stiffness of the wall, significantly impacting its response. This study evaluates the effect of opening size and placement location on the performance of reinforced concrete shear walls. The study quantifies the percentage change in natural frequency of RC walls when it increases or decreases. The investigation aims to identify openings that yield unfavorable outcomes and determine the optimal locations that meet the dynamic requirements of the walls more effectively efficiently. The findings reveal that the presence of openings, arranged in various configurations, can exert have both positive good and negative effects on the natural frequency of the walls. Consequently, this dynamic property can be subject to an increase of by up to 17% or a decrease of by up to 37%, depending on the arrangement of the openings.